Science Paradigms: Positivism, Rationalism, Empiricism, Criticism, and Constructivism - Maspuroh, Maspuroh; Moch Fadhil Alamsyah; Shaira Salsabila NS; Siti Hopipah (Bibliotheca: Journal of Philosophy, 2026)
Paradigms in the philosophy of science play a crucial role in shaping perspectives on the nature of knowledge, the sources of truth, and the methods for acquiring scientific understanding. This study examines five major paradigms in the philosophy of science—positivism, rationalism, empiricism, critical philosophy (criticism), and constructivism—with the aim of understanding their fundamental differences and points of convergence. Positivism emphasizes objective empirical observation; rationalism highlights the role of reason in shaping knowledge; while empiricism regards sensory experience as the primary source of knowledge. Critical philosophy, as a synthesis of rationalism and empiricism, asserts that knowledge results from the combination of reason and experience. Meanwhile, constructivism views knowledge as an active construction by individuals within a social and subjective experiential context. This study shows that understanding these various paradigms is essential for developing a holistic and critical scientific framework.